Superintendent leadership under shifting governance regimes. Issue 7 (19th August 2014) - Paulsen, Jan Merok; Johansson, Olof; Moos, Lejf; Nihlfors, Elisabet; Risku, Mika; Roberts, Brian; Arlestig, Helene
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This article analyzes the superintendent position, its relation to the local political system and the function as superior of principals in the school district in order to illuminate important district-level conditions for student learning. Influences from historical legacies and policy cultures are investigated by means of cross-country case analyses. Design/methodology/approach This article is based on data from national surveys of superintendent leadership in Sweden, Denmark, Finland and Norway. Findings A key point is the observation of a mix-mode system of hard and soft governance. Municipalities, schools, teachers and pupils are, yet in different degrees across the Nordic countries, subjected to external evaluation and assessment by central control agencies, where the streams of reports, assessments and performance data are assembled. However, shifts in the governance systems are only modestly reflected in in the self-reports on the superintendents' role. Overall, superintendents in the cases express a self-preferred leadership style as professional learning facilitators who focus on pupil orientation, which positions the superintendent in "crossfires" between conflicting stakeholder demands. Research limitations/implications The article reinforces the importance of superintendent leadership in local school governance. It underscores the importance that superintendents facilitate learning conditions for school leaders, teachers and students, which we see as a promising path for further research. Originality/value The article provides empirical evidence regarding superintendent leadership situated in local social and political contexts within the Nordic countries. The cross-country analysis illuminates how path-pendent historical legacies mediate current reform trends.